A sensemaking approach to a discursive ethical skill in healthcare management: the case of an oncopaediatric service. (1st January 2015) - Gagnou–Savatier, Emmanuelle; Mercier, Samuel
This study uses the case of an oncological paediatric service to discuss sensemaking and discourse ethics in the context of caregiving, building ethical competence to provide the best care possible to children. The patients and their families live in paediatric care, some for several years. At length, an intense relationship may develop between the medical staff and patients' family members, albeit at times a difficult relationship. Still, interviews conducted indicated that when caregivers provided the best care possible to these patients, even in this harsh environment, an ethics of sensitivity made a positive difference both for the patients and the medical staff. In the age of the newly passed Patient Protection Affordable Care Act in the USA often called Obamacare, this study shows there is such a notion as care and it does not need be legislated.